2017
DOI: 10.1016/j.jphs.2017.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 facilitates neurite outgrowth in a motor neuron-like cell line, NSC-34

Abstract: Prostaglandin E2 (PGE2) exerts various biological effects by binding to E-prostanoid receptors (EP1-4). Although recent studies have shown that PGE2 induces cell differentiation in some neuronal cells such as mouse DRG neurons and sensory neuron-like ND7/23 cells, it is unclear whether PGE2 plays a role in differentiation of motor neurons. In the present study, we investigated the mechanism of PGE2-induced differentiation of motor neurons using NSC-34, a mouse motor neuron-like cell line. Exposure of undiffere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…The role of caspase-3 activity in promoting neuronal differentiation was demonstrated across a broad spectrum of cell lineages including olfactory sensory neurons, neural stem cell, and PC12 cells [33]. Unlike these cells, previous studies of our and other laboratories revealed that the generation of cleaved caspase-3 is observed in undifferentiated NSC-34 cells as well as in differentiated forms [22,34]. Therefore, it seems that activation of caspase-3 is not responsible for the neuronal differentiation in NSC-34 cells.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The role of caspase-3 activity in promoting neuronal differentiation was demonstrated across a broad spectrum of cell lineages including olfactory sensory neurons, neural stem cell, and PC12 cells [33]. Unlike these cells, previous studies of our and other laboratories revealed that the generation of cleaved caspase-3 is observed in undifferentiated NSC-34 cells as well as in differentiated forms [22,34]. Therefore, it seems that activation of caspase-3 is not responsible for the neuronal differentiation in NSC-34 cells.…”
mentioning
confidence: 87%
“…The extent of cytotoxicity was quantified by measurement of lactate dehydrogenase (LDH) released into the medium during exposure to drugs. After NSC-34 cells had been incubated with PGE2 for 48 h, the supernatants were collected in new plates and LDH release was determined using a LDH-Cytotoxic Test kit (Wako Pure Chemical Industries) as described previously [22]. The absorbance of samples was measured at 570 nm using a microplate reader SH-1000Lab (Corona Electric).…”
Section: Ldh Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…PGE 2 promotes neuritogenesis in dorsal root ganglion neurons via EP2 (coupled to Gs protein) [14] and in sensory neuron-like ND7/23 cells via EP4 (coupled to Gs protein) [15]. Recently, our research has demonstrated that PGE 2 induces neurite outgrowth by activating EP2 in NSC-34 cells [16]. This suggests that PGE 2 is involved in neuritogenesis and the differentiation of various neurons including motor neurons.…”
Section: Introductionmentioning
confidence: 78%
“…Cultures were incubated at 37 • C and 5% CO 2 in a humidified atmosphere. For experimentation, NSC-34 cells were seeded onto Corning BioCoat™ Poly-L-Lysine TC-Treated Culture Dishes (Corning Inc., Corning, NY, USA) at a density of 12,500 cells/cm 2 and incubated for 24 h according to the method described previously [16].…”
Section: Cell Culturementioning
confidence: 99%